Edukasi Diet Seimbang pada Ibu Rumah Tangga sebagai upaya Pencegahan Penyakit Tidak Menular (PTM) di Desa Poto Kecamatan Moyo Hilir - Putri Adekayanti; Meliana Fitri; Abdul Hamid; Rafi’a Rafi’a (PPNI UNIMMAN, 2024)
Non-communicable diseases (NCDs) are chronic diseases, not transmitted from person to person. PTM has a long duration and generally develops slowly. Based on the results of interviews with housewives in Poto Village, information was obtained that people regularly consume vegetables, but fruit is still very rare. Side dishes include fish, tofu and tempeh and meat made in various variants. Consuming fast food such as instant noodles and fried foods is still a habit among people. Based on the background above, educational activities related to a balanced diet need to be conveyed to the public. This service aims to increase housewives' understanding of a balanced diet as an effort to prevent NCDs in Poto Village, Moyo Hilir District. Community service activities are carried out through providing education through health instructors using power point media. To evaluate the success of outreach activities in increasing housewives' knowledge about preventing NCDs, a series of pre-test and post-test activities were carried out. The results of the service show that there is an influence of the counseling given on increasing housewives' knowledge about a balanced diet as an effort to prevent NCDs.